Antioxidative and Anti‐UV Lignin Carrier for Peptide Delivery. Issue 2 (2nd December 2021) - Chee, Pei Lin; Sugiarto, Sigit; Yu, Yong; Tan, Ying Chuan; Ye, Enyi; Kai, Dan; Loh, Xian Jun
Abstract: Here, a sustainable antioxidant carrier based on lignin is developed to deliver palmitoyl tripeptide‐38. The poly(lignin/polyethylene glycol (PEG)/polypropylene glycol (PPG) urethane) is polymerized by randomly coupling lignin, PEG and PPG segment blocks using hexamethylene diisocyanate as a crosslinker. The derived poly(lignin/PEG/PPG urethane) loaded with palmitoyl tripeptide‐38, referred to as LM, is designed with careful considerations of both intrinsic and extrinsic causes of skin aging and a two‐way approach is taken on to effectively target the problem of skin aging. Upon exposure to the ultraviolet irradiation, LM successfully protects the cells by reducing the presence of reactive oxygen species, the damage to the antioxidant enzymes, and the expression of MMP‐1. Concurrently, LM also promotes the collagen production for skin repair. It is noteworthy that the collagen I content, in cells exposed to ultraviolet irradiation with LM‐4 and LM‐8 treatment (LM with 4 and 8 µg mL −1 palmitoyl tripeptide‐38, respectively), exceeds that of the control. Overall, this work successfully demonstrates a sustainable carrier with good antioxidant properties that effectively assisted the uptake of palmitoyl tripeptide‐38 by the cells. Abstract : Illustration of poly(lignin/polyethylene glycol/polypropylene glycol urethane) assisting the uptake of palmitoyl tripeptide‐38 by the cells leading to skin repair despite the ultraviolet radiation.